Alternatif Pemberantasan Buta Aksara Bagi Kaum Perempuan Berbasis Masjid - Rodiyah Rodiyah Rodiyah (Institut Agama Islam Negeri Bengkulu, 2018)
Literacy is a problem for various developing countries and among people who are still experiencing illiteracy are women, various strategies and theories used to eradicate literacy among the community. The author described an alternative to literacy eradication for mosque-based women using qualitative methods with a sociological approach. in this research it was found that the stronger the motivation and means of gathering such as mosques, the more opportunities for women to hone their abilities, especially in the field of literacy, would be more open.